Pengaruh Konsumsi Kurma (Phoenix Dactylifera) Terhadap Kenaikan Kadar Hemoglobin Pada Ibu Hamil Trimester Ii Di Wilayah Puskesmas Kediri - Eny Sendra; Susanti Pratamaningtyas; Ardi Panggayuh (coba, 2016)
Anemia in pregnancy is a national problem because it reflects the value of socio-economic welfare of society, and a very large influence on the quality of human resources. Pregnant anemia called "potential danger to mother and child", because that anemia require serious attention from all parties involved in health care at the forefront. Iron requirements of pregnant women increased so that it takes an additional 700-800 mg, among others, to improve haematopoesis 500 mg, 300 mg for the fetus needs to process haematopoesis during gestation, 200 mg for backup lost due to bleeding postpartum. It takes iron supplements around 30-60 mg per day. Dates contain real sugar in the form of glucose and fructose, rich in protein, fiber, minerals, such as iron, calcium, sodium, and potassium. Dates contained in hormone (potuchsin) are efficacious shrink the blood vessels in the uterus so that helps shrink the uterus and prevent postpartum uterine bleeding . Maturity dates are rich in calcium and iron, important in the formation of breast milk, as well as palm able to increase the quantity of breast milk and breastfeeding infants will have a sharp mind and good character. Levels of iron and calcium can replace the depleted force mother during childbirth or breastfeeding. Iron and calcium are two elective elements that are essential for the formation of blood and bone marrow). This study aimed to influence the consumption of date palm (Phoenix dactylifera) against the increase in hemoglobin levels in the second trimester pregnant women. The study design used quasy Experimental Design Non-Equivalent Control Group. The study population of pregnant women in the second trimester Puskesmas Ngadiluwih some 39 people. Samples were taken with quota sampling technique, and as many as 20 second-trimester pregnant women, aged 20-30 years, Hb lightweight category (9-10 g%), keep taking the tablets Fe for the respondents in this study, pregnant women not suffering from the disease / complications due to the disease. Exclusion criteria: the mother is not in place when the research berlangsung.Dari t test results obtained p value 0.245 is greater than alpha (0.05) which means there is no difference between the group dates with the control group. Key words: consumption of dates, levels of hemoglobin, the second trimester pregnant women